UPAYA PENINGKATAN KOMPETENSI PENYIDIK DIREKTORAT TINDAK PIDANA SIBER BARESKRIM POLRI DALAM MENANGANI KASUS CYBER CRIME (Jurnal Riset Manajemen Akuntansi Indonesia, 2023)
This research design uses a qualitative approach. The informants in this study were 3 members of the Criminal Investigation Unit of the Police consisting of 1 member of the Criminal Investigation Department and 2 personnel of the National Police Cyber Dittipid at the National Police Headquarters. While the object of research is the competence of investigators of the National Police Criminal Investigation Department in handling Cyber Crime Cases. The reason for the competence of the investigators of the Dittipidsiber Bareskrim Polri in handling Cyber Crime Cases still needs to be improved in terms of: (1) Aspects of attitude/personality (attitude), there are obstacles to public perception s that there are still unscrupulous Polri investigators. (2) Intellectuality/knowledge, there are still a small number of Polri investigators who do not understand the laws and regulations of criminal acts. (3) expertise/skills, there are still a small proportion who do not have basic investigative skills education (research vocational education/specialized vocational education) in handling cyber crime cases. Then efforts to improve the competence of the National Police Dittipidsiber Bareskrim investigators in handling Cyber Crime cases can be carried out by: (1) Attitude / Personality (Attitude) aspects by conducting mental training to Polri investigators on a regular basis, conducting regular ESQ (Emotional Spiritual Quotient) training. (2) Intellectuality/Knowledge by organizing professional investigative management training, disseminating new laws and regulations, sending good investigative personnel to attend investigation courses and investigative exercises, holding discussions, dialogues, workshops and seminars on investigative management. (3) Expertise/Skills by conducting training on the use and operationalization of computer and internet technology, making quick, easy and effective systems and administrative investigation methods, providing training on electronic evidence in cyber crime cases.
Keywords: competence; investigator; training